No effect of exogenous melatonin on development of cryopreserved metaphase II oocytes in mouse. Issue 1 (December 2015) - Li, Wei; Cheng, Keren; Zhang, Yue; Meng, Qinggang; Zhu, Shi'en; Zhou, Guangbin
Abstract Background This study was conducted to investigate effect of exogenous melatonin on the development of mouse mature oocytes after cryopreservation. Results First, mouse metaphase II (MII) oocytes were vitrified in the open-pulled straws (OPS). After warming, they were cultured for 1 h in M2 medium containing melatonin at different concentrations (0, 10−9, 10−7, 10−5, 10−3 mol/L). Then the oocytes were used to detect reactive oxygen species (ROS) and glutathione (GSH) levels (fluorescence microscopy), and the developmental potential after parthenogenetic activation. The experimental results showed that the ROS level and cleavage rate in 10−3 mol/L melatonin group was significantly lower than that in melatonin-free group (control). The GSH levels and blastocyst rates in all melatonin-treated groups were similar to that in control. Based on the above results, we detected the expression of geneHsp90aa1, Hsf1, Hspa1b, Nrf2 andBcl-x1 with qRT-PCR in oocytes treated with 10−7, or 10−3 mol/L melatonin and untreated control. After warming and culture for 1 h, the oocytes showed higherHsp90aa1 expression in 10−7 mol/L melatonin-treated group than in the control (P < 0.05); theHsf1, Hsp90aa1 andBcl-x1 expression were significantly decreased in 10−3 mol/L melatonin-treated group when compared to the control. Based on the above results and previous research, we detected the development of vitrified-warmed oocytes treated with either 10−7 or 0 mol/L melatonin byin vitro fertilization. No difference was observed between them. Conclusions Our results indicate that the supplementation of melatonin (10−9 to 10−3 mol/L) in culture medium and incubation for 1 h did not improve the subsequent developmental potential of vitrified-warmed mouse MII oocytes, even if there were alteration in gene expression.